Ventriculoscopic Surgery for Cystic Retrochiasmatic Craniopharyngiomas: Indications, Surgical Technique, and Short-Term Patient Outcomes. Issue 2 (18th August 2018) - Hollon, Todd C; Savastano, Luis E; Altshuler, David; Barkan, Ariel L; Sullivan, Stephen E
Abstract: BACKGROUND: Attempted gross-total resection for the management of cystic retrochiasmatic craniopharyngiomas can cause severe hypothalamic dysfunction and decrease overall survival. Ventriculoscopic surgery is a minimally invasive alternative; however, potential indications and technique have not been well defined. OBJECTIVE: To present our indications and technique for the ventriculoscopic treatment of cystic retrochiasmatic craniopharyngiomas. METHODS: We evaluated all patients with retrochiasmatic craniopharyngiomas for ventriculoscopic surgery. Indications and operative technique were developed to minimize operative morbidity, relieve mass effect, and optimize functional outcome. Cyst size and functional outcomes were statistically evaluated to determine radiographic and short-term clinical outcome. RESULTS: Indications for ventriculoscopic surgery included (1) radiographic evidence of hypothalamic involvement and (2) major cystic component. Ten patients met indications, and mean follow-up was 2.5 ± 1.6 yr. The surgical technique included wide cyst fenestration at the foramen of Monro, and fenestration of inferior cyst wall/third ventriculostomy ("through-and-through" technique). Preoperative Karnofsky performance status was 70 ± 15 and was inversely correlated with preoperative cyst size (13 ± 13 cm 3 ). A statistically significant reduction in cyst size was found on early postoperative imaging (2.1 ± 4.3 cm 3 ). Seven patients received postoperative radiotherapy. Postoperative performance scores (81 ± 8.3) had improved; no patient suffered functional decline. Pre- and postoperative body mass indices were similar. No patient had short-term hypothalamic obesity. CONCLUSION: Ventriculoscopic surgery, with or without adjuvant treatments, can reduce early postoperative tumor volume and improve short-term functional status in cystic retrochiasmatic craniopharyngiomas with hypothalamic involvement; it should be considered a minimally invasive option in the multimodal treatment of craniopharyngiomas. Further studies are needed to determine long-term efficacy.